SISTEM INFORMASI PENYULUHAN POSYANDU BERBASIS WEB MOBILE (Information Technology and Telematics, 2014)
Abstract-- Posyandu information system is to produce a series of activities to suit the needs of information is appropriate and timely for neighborhood health center manager. posyandu counseling  done posyandu cadres carrying books child health by collecting housewives or by visiting every house a cadre posyandu difficult because of the amount of information that must be given also time consuming and limited cadre posyandu itself. This can be overcome by building a system that can accommodate the information of cadre posyandu and display information to the user who wants to know about the neighborhood health center. The system will be built with PHP, jQuery, MySQL, and CSS. The system created will display on immunization of children, pregnant women, maternal and child health, child feeding, nutrition, stimulate the development of children. The system is also able to make decisions regarding the child's health early diagnosis, in this menu system provides information processing by changing the data, delete data and add data. With the development of mobile web system information contained in the system will be easily accessed and used Keywords-- Mobile Web, PHP, jQuery, MySQL, CSS, Counseling Information Systems Posyandu